Studies on mononuclear chelates derived from substituted Schiff bases ligands (Part 8): Synthesis and characterization of a new 5-chlorosalicyliden-p-aminoacetophenoneoxime and its complexes with Co(II), Ni(II), Cu(II) and Zn(II) - Canpolat, E (Polish Chemical Soc, 2005)
Co(L)(2), Ni(L)(2), Cu(L)(2) and Zn(L)(2) were synthesized from p-aminoacetophenoneoxime and 5-chlorosalicylaldehyde and Co(AcO)(2) center dot 4H(2)O or Ni(AcO)(2) center dot 4H(2)O or Cu(AcO)(2) center dot H2O or Zn(AcO)(2) center dot 2H(2)O in 1:2 molar ratio, employing a template approach. Based on elemental analyses, molar conductivity and magnetic susceptibility data, IR, H-1- and C-13-NMR and UV spectra, as well as thermal analyses (TG), a tetrahedral geometry for the complexes was determined. The data show that the ligand coordinates to the metal ion via -C=N- and -C-O- groups. All complexes are soluble in common organic solvents such as DMF and DMSO.
Keywords: Schiff bases; tetrahedral complexes